PANDANGAN TOKOH PERS TERHADAP ETIKA MEDIA BARU - Wahyudi Pratopo (Universitas Prof. Dr. Moestopo (Beragama), 2018)
This study seeks to reveal the opinion of Indonesian press leaders about the new media ethics in the digital age. The study uses descriptive qualitative method. Researcher collected data by studying documents and interviewing press leaders from the Indonesia Journalists Association and the Alliance of Independent Journalists. This study reveals that Indonesian journalists have had journalism code of ethics and cyber media guidelines, but they havent had the New Media Code of Ethics. The press leaders share the same view about journalism ethics, but they have different opinion about new media ethics.